THE EFFECT OF BIOGAS WASTE ON NUTRIENT CONTENTS AND MUSTARD PLANTS ( BRASSICA JU NCEA L.) PERFORMANCES - Junus, Mochammad; Nugroho, Hary; Pinandita, Eggipur; Fa'izah, Shafa; Fadilah, Dia (International Journal of Research -GRANTHAALAYAH, 2021)
The aim of research to determine the effect of sludge that mixed with plant waste and livestock waste on soil nutrient content and Brassica L. performances The research method used was the experiment of adding local microorganism solution (LMS) of banana weevil, coconut fiber ash and eggshell flour into sludge of quail and octopus waste as organic fertilizer with a completely randomized design (CRD) method with 6 treatments and 4 replications The treatments used consisted of P0: sludge 100%; P1 :sludge 50% + LMS 20% + Ash 10% + Eggshell Flour 20%; P2: sludge 50% + LMS 20% + Ash 12.5% ​​+ Eggshell Flour 17.5%; P3: sludge 50% + LMS 20% + Ash 15% + Eggshell Flour 15%; P4: sludge 50% + LMS 20% + Ash 17.5% + Eggshell Flour 12.5% and P5: sludge 50% + LM S 20% + Ash 20% + Eggshell Flour 10%. The result showed that the treatment given had a very significant effect (P <0.01) on the total N content, elements P and K, but the highest average was obtained from P0 (100% sludge), so it can be concluded that had no effect on nutrient content. The average of total N values ​​ranged from 1.15 ± 0.10 to 2.39 ± 0.40 percent, element P ranges from 2.65 ± 0.19 to 5.28 ± 0.19 percent and element K ranges from 1.08 ± 0.05 to 4.28 ± 0.21 percent. And for Brassica L. this treatment give a real effect (P <0.01) to the height and weight of a mustard plant wet and did not give an effect (P <0.05) to the number of leaves of mustard plants. The conclusion of this study are the mixed sludge waste had a significant effect on soil nutrient content and on Brassica L. performance.